El riesgo de que la propiedad horizontal se convierta en una comunidad de bienes o sociedad de hecho (2020)
This paper, arises as a result of one of the chapters of the master's thesis in private law, held at the University Santo Tomas in the city of Tunja, where I managed to conclude that commercial companies are legally similar to horizontal properties, to be able to apply a solution of this last regime of property to the regime of the corporations. In this chapter it is indicated that the solutions of one and another social regime are applicable to them, therefore they also succumb to the same fallacies of legal order, when some of their elements of existence, effectiveness and opposability are not present, thus the societies are deformed legally in de facto companies when any of these elements disappears or is not renewed or not remedied, converting the responsibility of limited order to an unlimited and joint liability, a legal reality that can be preached within horizontal properties with the same catastrophic effects for co-owners-partners, having the only difference in that in these occurs with the phenomenon called communities of goods and not de facto society. What generates among the co-owner’s responsibilities, no longer up to the amount of their contributions -including coefficients of co-ownership- but already in a solidary and unlimited manner. The research methodology used is the comparative documentary, taking as a macro conceptual framework the Colombian commercial code and Law 675 of 2001; The objective found was to demonstrate the risk and responsibility, which have the management councils of the P.h. and the legal representative or administrator, when by carelessness or negligence they do not comply with the annual obligations of registration and holding of assemblies.